Peningkatan Hasil Belajar IPS Siswa Kelas IV Di SDN 06 Kota Batusangkar Menggunakan Model Picture And Picture: Improving Social Studies Learning Outcomes for Class IV Students at SDN 06 Batusangkar City Using the Picture and Picture Model - Herlinda Sapitri; Yufi Latmini Lasari (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This research is a Classroom Action Research (CAR) which was carried out at SD Negeri 06 Batusangkar City with a total of 25 people, namely 13 boys and 12 girls. The research was conducted with the aim that the learning outcomes of fourth grade students at SDN 06 Batusangkar City would increase with the help of the Picture and Picture model, with 2 cycles of implementation. Collecting data using teacher and student observation sheets using tests in the form of questions. Cycle I obtained student learning outcomes and a percentage of 52% with an average score obtained from the total student learning outcomes of 74.8 (less). With the number of students who have completed as many as 13 people, and 12 others have not completed. Regarding the presentation in cycle II, it increased by 80% with an average score of 82 (good) with 20 students who completed and 5 students who had not completed. Regarding the observation of teacher activity in the first cycle by obtaining a score of 75 and in the second cycle a score of 88 was obtained. While the results of observations that were made regarding student activity in the first cycle obtained a score of 74.28 and in the second cycle it became better by obtaining a score of 82.85 . Thus the use of the Picture and Picture learning model can improve student learning outcomes from before.